SEMIOTICS OF COLOR RED IN THE GIVER MOVIE - Sudarwati, Emy; Zatalini, Nur Amalina (Lire Journal (Journal of Linguistics and Literature), 2019)
Color is a visual tool usually used in a movie which functions not only to make the movie looks good, but it is also to serve the story and build a character. Color brings a meaning behind its presences giving a sign that it can be interpreted accordingly. Chandler (2002) stated that sign is a meaningful unit which is interpreted as ‘standing for’ something other than itself.This current study analyzes the color red in The Giver movie as a sign based on semiotics approach. This study is a qualitative descriptive study. Document or content analysis is applied to analyze the captured scenes of The Giver movie whichcontains the color red. The study found out that the color red has several meanings behind its presences.The color is reflected in some properties. I found several things painted in color red around Jonas. The things are Viona’s hair, apples, books, and clothes.Even though the things have the same color red, each of them has different meaning beyond. The color red itself and the things that possess it have related meanings to complete each other. Also, the meaning of color red is closely related to Jonas’ character as the main character